THE MAZAPIL METEORITE: FROM PARADIGM TO PERIPHERY - Beech M. (My University, 2002)
The remarkable fact about the Mazapil meteorite is that it fell on the same night, in 1885, that the Andromedid meteor shower underwent a spectacular outburst. The simultaneity of these two events has driven speculation ever since. From ˜1886 to ˜1950 the circumstances of the Mazapil fall were taken, by a number of researchers, as the paradigm that demonstrated the fact that comets were actually swarms of meteoritic boulders. Beginning ˜1950, however, most researchers began to adopted the stance that the timing of the Mazapil fall was nothing more than pure coincidence. The reason behind this change in interpretation stemmed from, amongst other factors, the fact that none of the prominent annual meteor showers could be clearly shown to deliver meteorites. Also, with the introduction of the icy-conglomerate model for cometary nuclei, by F. Whipple in the early 1950s, it became increasingly clear that only exceptional circumstances would allow for the presence of large meteoritic bodies in cometary streams. Further, by the mid 1960s it had been shown that meteorites could, in fact, be delivered to the Earth from the main belt asteroid region via gravitational resonances. With the removal of the dynamical “barrier” against the delivery of meteorites from the asteroid region, the idea that the Mazapil meteorite could have been part of the Andromedid stream fell into complete disfavor. This being said, we nonetheless present the results of a study concerning the possible properties of the parent object to the Mazapil meteorite based upon the assumption that it was a member of the Andromedid stream. This study is presented to illustrate the point that while cometary showers do not yield meteorites on the ground, this does not, in fact, substantiate the argument that no meteoritic bodies reside in cometary streams. Indeed, we find no good reason to suppose that an object with the characteristics of the Mazapil meteorite could not have been delivered from the Andromedid stream. However, we argue that upon the basis of the actual reported observations and upon the scientific maxim of minimized hypothesis and least assumption it must be concluded that the timing of the fall of the Mazapil meteorite and the occurrence of the Andromedid outburst were purely coincidental.